ChemInform Abstract: Synthesis of Novel Dihydronaphthothiazine S, S‐Dioxides by Intramolecular Sulfonylamidomethylation of 2‐Naphthylmethanesulfonamides Using Amberlyst XN‐1010. Issue 21 (6th May 2016) - Sasiambarrena, Leandro D.; Canepa, Alicia S.; Bravo, Rodolfo D.
Abstract: The cyclization of sulfonamides (I) with s‐trioxane proceeds with high regioselectivity toward C1 of the naphthalene ring, while cyclization of the 1‐bromo derivative (IV) is directed toward C3.